AN EVALUATION OF PATIENTS DIAGNOSED WITH OPTIC NEURITIS IN CHILDHOOD - Mahmut Aslan; Serkan Kırık; Serdal Güngör (İstanbul Tıp Fakültesi Dergisi)
Objective: Optic neuritis (ON) is an autoimmune disease that starts with acute and subacute vision loss and is characterized by the demyelination of the optic nerve. It may appear as an isolated, idiopathic condition, or it may be a precursor of diseases such as Multiple Sclerosis (MS) or Neuromyelitis Optica (NMO). In the study, we aimed to evaluate ON patients and the longterm prognosis in pediatric patients. Material and Method: In this study, 13 patients who applied to the pediatric neurology clinic between years 2010-2017 and were diagnosed with acute ON were assessed retrospectively. Results: Thirteen patients diagnosed with ON were included in our study, six of whom were diagnosed with isolated ON (6/13, 46.15%). Nine of them were female. The average age of our patients was 12.8±3.07 years. Seven patients (53.85%) had unilateral involvement. A complete recovery was provided in 12 patients. There were recurrences in the follow-up of two patients, diagnosed with MS. Conclusion: ON should absolutely be considered in every child with blurred vision and vision loss. Early stage steroid treatment is the most efficient therapy.